El Pancho Torres se volvió esotérico (Homenaje) - Salgado Jácome, Pablo (2024)
In this text, the author intends to vindicate the poetry of an author who is totally unknown to new generations, Francisco Torres Dávila. After his texts appeared in several Ecuadorian literary magazines and he published two books of poetry, Torres Dávila kept a total literary silence; he stopped publishing and disappeared, by his own will, from the cultural panorama of the country. Recently the news of his death became known, hence the need to remember his literary work, as he is undoubtedly one of the most important poetic voices of his generation.